The Application of Grasshopper to Redesign Ship Hulls with a Parametric Approach Method Based on Delftship Reference - Eko Sasmito Hadi; Good Rindo; Berlian Arswendo Adietya; Muhamad Riza Alifviar; Hartono Yudo (International Journal of Marine Engineering Innovation and Research, 2024)
More than a year has passed since Francisco Pérez-Arribas (2023) introduced a parametric-based hull design method using Python scripts, beginning with the cross-sectional area (CSA) design. Several experimental studies have been carried out to improve the method and the quality of ship design. This study aims to generate an optimal hull design by utilizing normal vectors derived from the x and y vectors. These normal vectors are applied parametrically to determine the shape of the hull. The study also employs a cubic spline-based parametric technique for designing yacht hulls. The purpose of this study is to introduce the concept of parametric design through the development of visual programming used to form cross-sectional area curves and generate hull geometry. This study also discusses both the advantages and limitations of using visual programming approaches to accelerate the design process. By varying the CSA shape of the DelftShip model, the resulting parametric model has a high level of accuracy, with a difference of - 0.097016% in LCB and -0.28785% in volume when compared to the DelftShip model. results from Grasshopper reveal significant differences, particularly below a draft of 0.475, where the CP values from Grasshopper are lower than those from DelftShip. The parametric approach using normal vectors not only facilitates design exploration but also holds the potential to enhance overall hull design quality and optimization.